Studi Pendahuluan Sistem Akuakultur Cerdas Berbasis Online Monitoring Terhadap Unjuk Kerja Kincir Aerasi - Muh. Anis Mustaghfirin; Priyambodo Nur Ardi Nugroho; Dwi Sasmita Aji Pambudi; Eky Novianarenti (P3M Politeknik Negeri Cilacap, 2022)
This article discusses a preliminary study of developing a paddlewheel aerator for shrimp ponds using an integrated intelligent aquaculture system to support intensification. Two paddlewheel aerators with different phases have been successfully installed. The test was carried out on two different types of motors, which were intended to comprehend the performance of every motor on a paddlewheel aerator. The ratio of the speed values for a single-phase motor was 102 rpm and for a 3-phase motor was 110.3 rpm. The data from the performance observation of the aeration wheel motor can be viewed via a smartphone using a website application. The data displayed from the observations are in the form of data on voltage, current, frequency, power, power factor, and the power generated by the pinwheel motor. The test results show the performance of the aeration wheel motor that works under normal conditions with an average measurement error of 0.23%, below the acceptable error limit of 0.5%. This research forms the basis for a smart aquaculture system that can be developed domestically to support local industries in Indonesia.